2022
DOI: 10.1097/htr.0000000000000774
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Mobile Technology–Supported Diaphragmatic Breathing Intervention in Military mTBI With PTSD

Abstract: Background: Diaphragmatic breathing is an evidence-based intervention for managing stress and anxiety; however, some military veterans with mild traumatic brain injury (mTBI) and posttraumatic stress disorder (PTSD) report challenges to learning and practicing the technique. BreatheWell Wear assists performance of breathing exercises through reminders, biofeedback, and visual, tactile, and auditory guidance. Objective: To evaluate feasibility of implementing BreatheWell Wear, a mobile smartwatch application wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…The 6 articles included herein reflect both that TBI affects individuals across the life span and the myriad ways that various mHealth technologies can be potentially beneficial after TBI. These articles represent diverse technological solutions—including smartphone apps (all articles), wearable sensor technology,4,5 and conversational agents6—to address a variety of clinical applications, such as symptom monitoring,5,7,8 stress and symptom management,4,7,8 and behavior change 6,9. The studies in this issue echo many of the themes identified in recent reviews.…”
mentioning
confidence: 84%
See 4 more Smart Citations
“…The 6 articles included herein reflect both that TBI affects individuals across the life span and the myriad ways that various mHealth technologies can be potentially beneficial after TBI. These articles represent diverse technological solutions—including smartphone apps (all articles), wearable sensor technology,4,5 and conversational agents6—to address a variety of clinical applications, such as symptom monitoring,5,7,8 stress and symptom management,4,7,8 and behavior change 6,9. The studies in this issue echo many of the themes identified in recent reviews.…”
mentioning
confidence: 84%
“…Some articles highlight examples of mHealth solutions that have been designed to pair with traditional clinician-delivered interventions in a hybrid model. 5,6,9 The mHealth apps in the study by Juengst et al 9 were designed to complement and promote ongoing engagement in 2 intensive healthy lifestyle interventions. RehaBot 6 is designed to pair with a clinician-delivered behavioral activation treatment of depression providing support and reminders for completing planned activities between sessions with a therapist.…”
Section: Andmentioning
confidence: 99%
See 3 more Smart Citations